2016
DOI: 10.1007/s10096-016-2582-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of penicillin-binding protein 2b, 2x and 1a sequences in Streptococcus pneumoniae isolates causing invasive diseases among children in Northeast China

Abstract: Streptococcus pneumoniae is one of the common pathogens causing severe invasive infections in children. This study aimed to investigate the serotype distribution and variations of penicillin-binding proteins (PBPs) 2b, 2x and 1a in S. pneumoniae isolates causing invasive diseases in Northeast China. A total of 256 strains were isolated from children with invasive pneumococcal disease (IPD) from January 2000 to October 2014. All strains were serotyped and determined for antibiotic resistance. The amplicons of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 40 publications
6
19
2
Order By: Relevance
“…Previous studies have suggested that PBP1a, − 2x, and − 2b are generally recognized as the major PBPs associated with the activities of penicillins and some cephalosporins [ 4 , 12 ]. In our study, changes found in PBP1A, PBP2b and PBP2X are globally similar to those previously reported [ 6 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous studies have suggested that PBP1a, − 2x, and − 2b are generally recognized as the major PBPs associated with the activities of penicillins and some cephalosporins [ 4 , 12 ]. In our study, changes found in PBP1A, PBP2b and PBP2X are globally similar to those previously reported [ 6 , 13 , 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…The maximal level of resistance of PNSP responsible of invasive pneumococcal disease reported in Casablanca, is relatively low with the maximal MICs = 2 mg/L compared to MICs of PNSP in many countries where MICs ≥ 8 mg/L were reported [ 14 , 15 ]. Our investigation of the PBP1a, − 2x, and − 2b amino acid sequences of 30 clinical pneumococci demonstrates that the degree of diversity within these amino acid sequences correlates with increasing resistance to β-lactam antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Significant reduction of PNSP occurred in several countries after the use of PCV [1923]. The maximal level of resistance of PNSP responsible of IPD is relatively low with MICs = 2 mg/L compared to MICs of PNSP in many countries where MICs ≥ 8 mg/L were reported [4, 24]. Serotypes among PNSP were mainly 6B, 14, 19A, 19F and 23F in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Pneumococcal resistance to β-lactams has been attributed to alterations of the penicillin-binding proteins (PBP) which reduce their affinity [4]. The first pneumococcal isolate resistant to penicillin was reported in 1967 from a patient in Australia [5], and resistant pneumococci have subsequently increased in prevalence worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation